Pengaruh Pengunduran Diri Jack Ma terhadap Return Saham Baba (Studi Kasus: Alibaba Group Holding Limited) - Wulandari, Dwi Susanty; Ismail, Andy (Universitas Darwan Ali, 2020)
This study aimed to analyze whether Jack Ma’s resignation hurt BABA stock returns. This research is Jack Ma’s resignation event study from Alibaba Group Holdings Limited (10 September 2018). The 5-month research sample began on May 1, 2018, to September 28, 2018. In the 1-day and 3-day window the result showed that Jack Ma’s resignation had a significant adverse effect on BABA stock returns, but no longer affected the following day.